The Relationship Of E-Government And Working Performance Of Civil Servant Od Pidie District Government - Rahmat Musfikar (Politeknik Negeri Lhokseumawe, 2020)
One of the programs in Communication Information Technology in the government field is the implementation of E-Government. During this digital era, efforts to implement e-government are being actively carried out by public or government bureaucracy to improve services to the public and governance. Pidie district government has begun implementing e-government, one of which is through Pidie District Head Regulation No. 53 of 2018 concerning the Implementation of e-Perfomance in Pidie District Government Unit in which it is a part of e-government. Pidie Government through Pidie Regency Personnel and Human Resources Development Agency (BKPSDM) has begun to socialize e-government implementation by disseminating e-performance applications to the civil servantin Pidie District Apparatus Work Unit. This research was conducted to see the relationship between e-government implementation and the performance of the Civil servantin the Pidie District Government. This research used a combination method approach using sequential explanatory design. The data collection technique used in this study was the distribution of questionnaires to 22 Civil servant (ASN) in the Central Government Office of Pidie District, the Regional Secretariat of Pidie District, an office directly related to employment, namely BKPSDM. The sampling of this research is purposive sampling which is a non-random sampling or nonprobability sampling. Processing data using Partial least square (PLS) analysis which is a multivariate Structural Equation Modeling (SEM) data analysis method. In the PLS analysis method there are three stages of evaluation, first evaluating the outer model, second evaluating the inner model, and finally testing the hypothesis. The results of the final evaluation of hypothesis testing can be concluded that the implementation of E-Government has a significant relationship with improving the state civil apparatuses performance of the Pidie District Government with a contribution of 79.7%.